PENGARUH SUHU DAN LAMA THAWING DI DATARAN RENDAH TERHADAP KUALITAS SEMEN BEKU SAPI SIMMENTAL - Nani Aprilina; Sri Suharyati; Purnama Edy Santosa (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
The purpose of this study was to determine temperature and duration of thawing in thelowlands the frozen semen of Simmental Cattle most optimal for use in IB. The study was conductedin March 2014, research was conducted using a completely randomized design with a 3x3 factorial.The first factor is the temperature (34°C, 37°C, and 40°C) and Factor II thawing time (10 seconds, 15seconds, and 20 seconds) with 3 replications. Parameters observed in this study is the motility ofspermatozoa and percentage of live spermatozoa. The data were analyzed using ANOVA andDuncan's test further the 5% level.The results showed that temperature and thawing significant (P<0,05) on sperm quality frozensemen of Simmental cattle, but has no interaction between them. Results of Duncan test (P<0,05) tothe most good quality spermatozoa obtained at 37ºC thawing temperatures, and thawing at 15 secondslong. Motility of spermatozoa at thawing temperatures 37ºC is 38.33% and thawing 15 seconds longis36.11%. The percentage of live spermatozoa at thawing temperatures 37ºC is40.78% and thawing 15seconds long is 38.33%.